2019
DOI: 10.1093/geront/gnz044
|View full text |Cite
|
Sign up to set email alerts
|

Shades of Blue and Gray: A Comparison of the Center for Epidemiologic Studies Depression Scale and the Composite International Diagnostic Interview for Assessment of Depression Syndrome in Later Life

Abstract: Background and Objectives Psychiatric research lacks the equivalent of a thermometer, that is, a tool that accurately measures mental disorder regardless of context. Instead, the psychometric properties of scales that purport to assess psychopathology must be continuously evaluated. To that end, this study evaluated the diagnostic agreement between the eight-item Center for Epidemiologic Studies Depression Scale (CESD-8) and the Composite International Diagnostic Interview—short form (CIDI-SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…This scale estimates a probable psychiatric diagnosis of major depression and has been validated in field settings and widely used in population-based health surveys [ 42 ]. The scale is a fully-structured diagnostic interview based on the Diagnostic and Statistical Manual of Mental Disorders (DSM) criteria for major depressive episode and validated in field settings especially by non-clinicians in general population surveys and in cross-cultural settings [ 46 48 ]. Cronbach’s alpha indicated that CIDI-SF has an acceptable level of reliability (α = 0.68).…”
Section: Methodsmentioning
confidence: 99%
“…This scale estimates a probable psychiatric diagnosis of major depression and has been validated in field settings and widely used in population-based health surveys [ 42 ]. The scale is a fully-structured diagnostic interview based on the Diagnostic and Statistical Manual of Mental Disorders (DSM) criteria for major depressive episode and validated in field settings especially by non-clinicians in general population surveys and in cross-cultural settings [ 46 48 ]. Cronbach’s alpha indicated that CIDI-SF has an acceptable level of reliability (α = 0.68).…”
Section: Methodsmentioning
confidence: 99%
“…This scale estimates a probable psychiatric diagnosis of major depression and has been validated in field settings and widely used in population‐based health surveys 28 . The scale is a fully structured diagnostic interview based on the Diagnostic and Statistical Manual of Mental Disorders (DSM) criteria for major depressive episode and validated in field settings especially by non‐clinicians in general population surveys and in cross‐cultural settings 29–31 . Cronbach's alpha indicated that CIDI‐SF has an acceptable level of reliability ( α = 0.68) 32 …”
Section: Methodsmentioning
confidence: 99%
“…28 The scale is a fully structured diagnostic interview based on the Diagnostic and Statistical Manual of Mental Disorders (DSM) criteria for major depressive episode and validated in field settings especially by non-clinicians in general population surveys and in cross-cultural settings. [29][30][31] Cronbach's alpha indicated that CIDI-SF has an acceptable level of reliability (α = 0.68). 32…”
Section: Depression (Cidi-sf)mentioning
confidence: 99%
“…Higher scores indicate more depressive symptoms. Consistent with previous work ( Dang et al, 2020 ; Steffick, 2000 ), a binary variable was used to identify those middle- to old age black men who reported three or more depressive symptoms relative to those middle- to old age black men who reported fewer than three depressive symptoms.…”
Section: Methodsmentioning
confidence: 99%